Pneumonias in the elderly patient. Risk factors and poor prognosis - Luis Alberto Santos Pérez; Diannys Hernández Cabeza; Cándida Grisel Milián Hernández; Kevin Ronald Santos Milián (Acta Médica del Centro, 2021)
Introduction: pneumonia, named by Sir William Osler “the captain of the hosts of men's death”, represents one of the main health problems in the world. Both the incidence and the mortality rate increase with age because in the geriatric patient there are diseases that increase the risk of pneumonia. In addition, due to their own health conditions and immune senescence, the probability of dying from this cause is very high. Objective: to study the main characteristics of pneumonia in the elderly and mainly the increased risk factors for developing it. Methods: a prospective quantitative-qualitative research was carried out in 950 patients aged 60 years or older with a diagnosis of community-acquired pneumonia admitted to the “Arnaldo Milián Castro” Hospital, in Villa Clara Province, from January 2016 to December 2018 with the aim of determining the risk factors of community-acquired pneumonia in the elderly. Results: the most frequent clinical manifestations were: fever, cough, decay, tachypnea and tachycardia, in various combinations. Smoking, chronic obstructive pulmonary disease, bronchial asthma, heart failure, diabetes mellitus and alcoholism were risk factors. Age was an independent prognostic factor associated with higher mortality, longer hospital stay and longer recovery time. Conclusions: the most frequently found risk factors were smoking, alcoholism, chronic obstructive pulmonary disease, cancer, diabetes mellitus and heart failure.